Electronic commerce 2018 : a managerial and social networks perspective /: a managerial and social networks perspective. ([2018]) - Turban, Efraim; Outland, Jonathan; King, David R; Lee, Jae Kyu; Liang, Ting-Peng; Turban, Deborrah C
No abstract available